Perceived Organizational Support and Work Engagement Between The Health Service Sector - Fariha azzahra; Indah rahayu; Sri Martono (LPPM Universitas An Nuur, 2022)
Background: First line managers have an important role in the management system of health care organizations because they provide support and bridges for senior management and their employees. Work engagement forms the basis of the facility's function that creates organizational goals and approaches to patient care, but also meets the expectations and needs of subordinate staff. Purpose: The aim of the study was to examine the relationship between perceived organizational support and work engagement of first-line managers in the health care sector Methods: Collecting data using a questionnaire from a private hospital in Purwodadi. The research method uses SPSS to analyze the direct effect. Conclusion: The results show a positive and significant relationship between perceived organizational support and work engagement, so that it can increase the interest of firstline managers in hospitals to strengthen work engagement with higher job performance and job satisfaction. Suggestion: This study examines work engagement as the dependent variable, although work engagement is often used as a determining variable. In future research, it is possible to examine the potential effect of Perceived Organizational Support and work engagement with other variables such as job satisfaction and performance.